2019
DOI: 10.1111/ans.15487
|View full text |Cite
|
Sign up to set email alerts
|

Window of opportunity treatment in breast cancer

Abstract: Window of opportunity therapies, which involve short‐term administration of systemic therapy between cancer diagnosis and surgery, have raised significant interest in recent years as a mean of assessing the sensitivity of a patient's cancer to therapy prior to surgery. There is now compelling evidence that in patients with early stage hormone‐receptor positive breast cancer, a 2‐week preoperative treatment with standard hormone therapies in a preoperative window period provides important prognostic information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Pathologic complete response (pCR) has been considered the most vital clinical parameter for the prediction of outcomes after neoadjuvant chemotherapy 42. However, in a meta-analysis by Spring and colleagues showed that there was no association between pCR and event free survival in HR + , HER2 − breast cancer after neoadjuvant chemotherapy, unlike hormone negative breast cancer and HER2 + subtypes where pCR is a known, important predictor of outcome (hazard ratio: 0.15, CI: 0.02-1.10; n = 3385) 43…”
Section: Predictors Of Endocrine Sensitivity In Neoadjuvant Settingmentioning
confidence: 99%
“…Pathologic complete response (pCR) has been considered the most vital clinical parameter for the prediction of outcomes after neoadjuvant chemotherapy 42. However, in a meta-analysis by Spring and colleagues showed that there was no association between pCR and event free survival in HR + , HER2 − breast cancer after neoadjuvant chemotherapy, unlike hormone negative breast cancer and HER2 + subtypes where pCR is a known, important predictor of outcome (hazard ratio: 0.15, CI: 0.02-1.10; n = 3385) 43…”
Section: Predictors Of Endocrine Sensitivity In Neoadjuvant Settingmentioning
confidence: 99%